The role of adjuvant radiotherapy for breast cancer patients with axillary node negative or limited nodal disease after total mastectomy, axillary nodal clearance and systemic therapy - Van Jaarsveld, Albert (Division of Radiology, 2014)
Includes bibliographical references.